Expansion of Sikh State under Ranjit Singh: The Rise and Influence of Ranjit Singh's Sikh State (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This present paper makes that how Ranjit Singh make Maharaja and conquest the most of the North-West frontier. This paper also tells about the quality of Ranjit Singh’s army and his coutries. This is also tells Ranjit Singh’s relation with Britsher, Maratha, Afghans and other cities.